Discipleship and unity: Bonhoeffer's ecumenical theology - Jodon, Cole (Lexington Books/Fortress Academic, 2022)
"In Discipleship and Unity: Bonhoeffer's Ecumenical Theology, Cole Jodon presents Bonhoeffer's ecumenical theology - a theology grounded in an understanding of the church as the person of Christ, and practiced in active obedient discipleship"--